The Concrete Control Model of Constitutionality in the Ecuadorian Constitution 2008 - López Hidalgo, Sebastián (2022)
This text highlights the type of constitutional control in Ecuador from the constitutional design of 2008. After briefly exposing the origins of constitutional control, its classics (concentrated/European control and diffuse/American constitutional control), and as it has given way to a hybridization of the same, transcending the explanations of geographical and political origin of the models, the article focuses on the institution called the norm consultation as a concrete constitutional control mechanism, inserted in the Current Constitution. From a comprehensive reading of the fundamental text, the ordinary legislation and some central rulings of the Constitutional Court on the subject, the text suggests that there has been an important turn in the original version of said institution (control of constitutionality in consultation of normative ), which initially has been described as a concentrated control of constitutionality, opening the way to a new discussion, by way of jurisprudence, on a type of control of mixed constitutionality as established at the time by the Ecuadorian Constitution of 1998. This fact It demonstrates the importance of constitutional jurisprudence within the source system, while it allows knowing the new horizons on the discussion in the Ecuadorian case.